Hemostatic changes in Vietnamese children with mild dengue correlate with the severity of vascular leakage rather than bleeding. - Wills, B; Tran, V; Nguyen, T; Truong, T; Tran, T; Nguyen, MD; Tran, V; Nguyen, V; Dinh, T; Farrar, J (2009)
The mechanisms underlying the bleeding manifestations and coagulopathy associated with dengue remain unclear, in part because of the focus of much previous work on severe disease without an appropriate comparison group. We describe detailed clinical and laboratory profiles for a large group of children with dengue of all severities, and a group with similar non-dengue febrile illnesses, all followed prospectively from early presentation through to recovery. Among the dengue-infected patients but not the controls, thrombocytopenia, increased partial thromboplastin times and reduced fibrinogen concentrations were apparent from an early stage, and these abnormalities correlated strongly with the severity and timing of vascular leakage but not bleeding. There was little evidence of procoagulant activation. The findings do not support a primary diagnosis of disseminated intravascular coagulation to explain the intrinsic coagulopathy. An alternative biologically plausible hypothesis is discussed.